1984
DOI: 10.1111/j.1365-2621.1984.tb14961.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition of Lamb of Two Age Groups

Abstract: The nutrient composition of Spring and Fall lambs were investigated. Seven retail cuts from carcasses of lambs raised under commercial conditions, and representing two age groups (4-4s mo and 8-P mo) were analyzed in both raw and cooked form. Separable lean meat was analyzed for proximate composition, 8 vitamins, 8 inorganic nutrients, cholesterol and 12 fatty acids. Except for moisture, total lipid, riboflavin, niacin, Zn and Fe, there were no practical differences in nutrients between cuts or age groups. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
21
2
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 13 publications
11
21
2
1
Order By: Relevance
“…The loin cut had the highest zinc content, although not significantly, when compared to the leg and the shoulder. These results contrasted the findings of the study by Ono et al (1984), where the blade chop (shoulder cut) showed the highest value for zinc and the loin chop the lowest.…”
Section: Cooked Cutscontrasting
confidence: 57%
See 1 more Smart Citation
“…The loin cut had the highest zinc content, although not significantly, when compared to the leg and the shoulder. These results contrasted the findings of the study by Ono et al (1984), where the blade chop (shoulder cut) showed the highest value for zinc and the loin chop the lowest.…”
Section: Cooked Cutscontrasting
confidence: 57%
“…Maturity of animals influences the meat fatty acid composition. Ono et al (1984), studied lambs from two age groups and found that lambs from younger animals had higher amounts of some of the saturated fatty acids, and a higher polyunsaturated/saturated fatty acid ratio than those of older animals.…”
Section: Raw Cutsmentioning
confidence: 99%
“…The nutrient value of cooked meat is more useful than raw as the cooked meat show actually consumed meat (Ono et al, 1984). However, the raw value was used to evaluate the effect of husbandry practices, production and marketing on the nutrient composition of the muscles (Sainsbury, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There were small variations between dromedary camel muscles for vitamin B 12 concentrations, with the range from 4.13 to 4.77 µg/100 g. Fifty grams of dromedary camel meat will contain 2.23 g/100 g vitamin B 12 , which represents 112% of the RDA for vitamin B 12 . The camel meat contained more vitamin B 12 than sheep (0.25 mg/100 g) and veal meats (0.18 mg/100 g) (Ono et al 1984(Ono et al , 1986. Vitamin B 2 content varied between camel muscles and ages from 0.20 to 0.26 mg/100 g (Table 6).…”
Section: Vitaminsmentioning
confidence: 99%